PENGEMBANGAN BAHAN AJAR BERBASIS WEB MENGGUNAKAN WORDPRESS PADA PEMBELAJARAN MATEMATIKA KELAS X MIPA SMA NEGERI 2 PADANG - RESY ISWARI (Departemen Matematika, 2021)
This study aims to develop web-based teaching materials using wordpress in mathematics learning class X MIPA SMA, determine the level of validity and practicality of web-based teaching materials using wordpress in mathematics learning class X MIPA SMA. This research is included in the research and development of R&D with the Dick & Carey model. The resulting product is a web-based teaching material using wordpress on Trigonometry material. This teaching material is validated by two lecturers and one math teacher as a material expert. The level of practicality of web-based teaching materials using wordpress is determined by 40 students of class X MIPA 6 SMA Negeri 2 Padang. Data collection is done by filling out questionnaires. The result of this research is web-based teaching materials using wordpress developed with Dick & Carey procedure, which is the stage of needs analysis; product design stage; validation and evaluation stage; and the final product stage. Web-based teaching materials using wordpress can be accessed on https://handalmatematika.wordpress.com/2021/01/23/trigonometri/. Validation obtained from the material expert has a final value of 79% and belongs to the valid category. While practicality obtained from 40 learners has a final score of 79.53% and belongs to the practical category. Thus, web-based teaching materials using wordpress on mathematics learning materials Trigonometry class X MIPA SMA valid and practical to be used as a source of learning wherever it is. Keywords – Teaching Materials, WordPress, Mathematics Learning.